(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
For sufficiently important attention to the issues of performance and factors of achieving the result at the competitions of various levels in sports martial arts, research on the karate material was not carried out, which is the relevance of this study. Purpose: to find out the results of the performances of Ukrainian punaratists in the Series A competitions (WKF) during 2018-2022. Methods: Theoretical analysis and generalization of data, analyzing documentary materials, methods of mathematical statistics. The protocols of international competitions series A from karate during 2018-2022: 2018 competitions took place in the cities of Shanghai, Guadalajara, Salzburg; 2019 – Salzburg, Istanbul, Montreal, Santiago; 2020 – Chile, Istanbul, Dunstan; 2021 – the competition was not carried out; 2022 – Pamplona, Cairo, Kocaeli, Jakarta. The results are taken into account in weight categories -60, -67, -75, -84, +84 among men and -50, -55, -61, -68, +68 among women. Results. The total number of participants in the racing series A of karate ranges from 40 to 222 athletes. The highest number of participants is present in the weight category -67 kg among men, the lowest - in the category of women +68 kg. Ukrainian athletes regularly participate in series A competitions and demonstrate high results. The most successful Ukrainian athletes in the competitions Series A is A. Terelyuga (w.k.: -55 kg) and Lvivian S. Goruna (w.k.: -75 kg). They regularly combat prize places at separate stages. Successfully acted Ukrainian athletes in V.K.: -61 kg - A. Seriyogin and O. Sholokhov, among Lvivs: In w.k.: -68 kg - G. Melnyk and w.k..: -50 kg K. Solomia. Among men in different weight categories also regularly combat prize places in the competitions of Series A: I. Pak, D. Yanovsky and V. Sonnyh. Conclusions. Participation in Series A competitions is important for athletes, since they allow them to gain rating points and improve their positions in the world rating WKF. An analysis of the performances of athletes in competitions is an important direction of scientific research. It allows you to get valuable information about the peculiarities of training athletes, their strengths and weaknesses, trends in the development of certain sports and sports as a whole; is an important tool for trainers, athletes.